VIRTUAL REALITY IN MEDICAL EDUCATION: THE IMPACT ON PROFESSIONAL SOCIALIZATION AND EMPATHY - A NARRATIVE REVIEW - Ożga, Sebastian; Tryczyński, Piotr; Sałak, Jakub; Helbin, Piotr; Wrona, Jakub; Laskowska, Wiktoria; Donocik, Wiktoria; Kwolek, Klaudia; Pilarek, Marcel; Spirkowicz, Aleksandra (International Journal of Innovative Technologies in Social Science, 2026)
Background: Medical education is experiencing a digital transformation, moving from the traditional "See One, Do One, Teach One" apprenticeship model toward immersive Simulation-Based Medical Education(SBME). This narrative review explores how Virtual Reality (VR) acts as a transformative catalyst to reshape the professional socialization and clinical attitudes of future physicians. Methods: The study utilizes a narrative review methodology, synthesizing interdisciplinary research identified through a multi-stage search of global bibliographic databases. The analytical framework employs a thematic synthesis approach, utilizing the four-level Kirkpatrick model to evaluate educational reactions, learning, behavior, and results. Specialized themes categorize interventions based on their impact on professional identity formation and both cognitive and affective empathy. Results: Findings demonstrate that VR serves as a scalable bridge between theory and practice, enhancing psychomotor skills, spatial orientation, and patient safety. Immersive virtual embodiment allows students to experience patient perspectives, fostering ethical internalization and empathy. However, the data highlights a persistent "empathy gap" where technical efficiency might lead to desensitization. Furthermore, a "digital divide" manifests through high implementation costs, reinforcing educational hierarchies between high-income and resource-limited institutions. Conclusion: VR facilitates a profound paradigm shift by standardizing clinical training and promoting global professional socialization. While offering significant pedagogical benefits, the sustainability of relational gains remains a recognized gap requiring longitudinal validation. Future integration with Artificial Intelligence and haptic feedback is essential to balance technological innovation with the humanistic, patient-centered dimensions of medical practice.